1998
DOI: 10.1089/thy.1998.8.155
|View full text |Cite
|
Sign up to set email alerts
|

Combined Impairment of Nutritional Parameters and Thyroid Homeostasis in Mildly Iodine-Deficient Children

Abstract: The relation between thyroid homeostasis and the biochemical parameters of subclinical protein malnutrition has been analyzed in schoolchildren in a rural area in the south of Italy, known to be moderately iodine-deficient. The sera of 32 children (15 males and 17 females aged 6 to 11 years) have been analyzed. These children were divided into two groups, according to thyroid function: (1) 16 euthyroid children (mean thyrotropin [TSH] 2.38 +/- .35 mU/L; 6 with goiter) and (2) 16 subclinical hypothyroid childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In addition to most of the factors listed in Table 1, the levels of these proteins are affected by levels of their physiologic ligands: iron in the case of transferrin and retinol (vitamin A) for RBP (34). In the presence of iodine deficiency with elevated thyroid stimulating hormone (TSH) levels, RBP levels are proportionately lower (35). Although transferrin levels fall markedly during starvation (21), studies in children with severe PEM have shown only fair correlation between plasma transferrin levels and clinical indices of wasting (36).…”
Section: Other Plasma Proteinsmentioning
confidence: 99%
“…In addition to most of the factors listed in Table 1, the levels of these proteins are affected by levels of their physiologic ligands: iron in the case of transferrin and retinol (vitamin A) for RBP (34). In the presence of iodine deficiency with elevated thyroid stimulating hormone (TSH) levels, RBP levels are proportionately lower (35). Although transferrin levels fall markedly during starvation (21), studies in children with severe PEM have shown only fair correlation between plasma transferrin levels and clinical indices of wasting (36).…”
Section: Other Plasma Proteinsmentioning
confidence: 99%
“…Similarly lower weight and height of children with goiter compared to their healthy peers in this study indicates the presence of nutritional insuffi ciency in children with palpable goiter. Centanni reported that even mild protein-energy malnutrition may have detrimental eff ects on thyroid homeostasis in iodine-deficient areas ( Centanni et al, 1998 ). Long lasting insuffi cient nutrition causes cessation of growth and results in nutritional growth retardation (NGR).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, PEM may contribute directly to goitrogenesis through the lack of substrate availability, particularly essential amino acids such as tyrosine 21 . Even mild PEM is reported to have detrimental effects on thyroid homeostasis in iodinedeficient areas 22 . Goitre detection rate was highest in children with low and especially very low socio-economic status.…”
Section: Discussionmentioning
confidence: 99%
“…A low weight-for-age Z-score (WAZ) (, -2SD) is considered to indicate underweight in the absence of significant wasting 10 -12 . In addition, BMI values less than 15 kg m 22 indicate total body fat content below 5% of body weight. That BMI is an important index of being thin was interpreted in children over 10 years of age 13 .…”
Section: Data Collectionmentioning
confidence: 99%